Partial Recovery of Alcohol Dependence-Related Deficits in Sleep Evoked Potentials Following 12 Months of Abstinence - Colrain, Ian M.; Padilla, Mayra L.; Baker, Fiona C. (Frontiers in Neurology, 2012)
Stimuli presented during sleep can produce an evoked EEG delta wave referred to as a K-complex. These responses occur when large numbers of cortical cells burst fire in a synchronized manner. Large amplitude synchronized scalp responses require that the CNS contain large numbers of healthy neurons that are interconnected with highly functional white matter pathways. The P2, N550 and P900 components of the evoked K-complex are sensitive measures of normal healthy brain aging, showing a decrease in amplitude with age. N550 and P900 amplitudes are also reduced in recently detoxified alcoholics, most dramatically over frontal scalp regions. The present study tested the hypothesis that the amplitude of K-complex related evoked potential components would increase with prolonged abstinence. Fifteen alcoholics (12 men) were studied twice, separated by a 12-month period, during which time they were followed with monthly phone calls. Subjects were aged between 38 and 60 years at their first study. They had on average a 29.3 ± 6.7 year drinking history and had been abstinent for between 54 and 405 days at initial testing . Evoked K-complexes were identified in the EEG and averaged to enable measurement of the P2, N550 and P900 peaks. Data were collected from 7 scalp sites (FP1, FP2, Fz, FCz, Cz, CPz and Pz). There were significant increases in, N550 and P900 amplitudes over 12 months. N550 and P900 also showed highly significant site by night interactions with the largest increases occurring over prefrontal and frontal sites. The substantial recovery in N550 amplitude with abstinence over a 12-month period is in contrast to the 1.5μV decrease predicted by the normal aging regression model, and an improvement of at least 5μV occurred in 11 of the 15 subjects. The data indicate that the sleep evoked response may provide a sensitive marker of brain recovery with abstinence from alcohol.